2022
DOI: 10.1080/21655979.2022.2084484
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal circRNA FNDC3B promotes the progression of esophageal squamous cell carcinoma by sponging miR-490-5p and regulating thioredoxin reductase 1 expression

Abstract: Exosomal circular RNAs (circRNAs) have been reported to play critical roles in esophageal squamous cell carcinoma (ESCC). We aimed to investigate the function of exosomal circRNA FNDC3B (circFNDC3B). The RNA levels and protein levels were examined using RT-qPCR and western blot (WB) assays. Colony formation and EdU assays were used to assess cell proliferative ability. Cell migratory and invasive abilities were detected by wound healing and transwell assays. Cell apoptosis was measured by flow cytometry. Glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…CircRNA refers to a type of non-coding RNA, which plays a biological regulatory role mainly through gene regulation [27][28][29] . Since circRNAs do not possess sensitive 5' and 3' ends, they show resistance to endonuclease degradation, thus making them remain more stable than linear RNAs and making them extremely abundant in the cytoplasm [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA refers to a type of non-coding RNA, which plays a biological regulatory role mainly through gene regulation [27][28][29] . Since circRNAs do not possess sensitive 5' and 3' ends, they show resistance to endonuclease degradation, thus making them remain more stable than linear RNAs and making them extremely abundant in the cytoplasm [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al. found circFNDC3B was upregulated in ESCC tissues and ESCC-derived exosomes ( 76 ). The knockout expression of circFNDC3B in exosomes significantly inhibited the growth of co-incubated tumor cells.…”
Section: The Roles Of Circfndc3b In Cancersmentioning
confidence: 99%
“…Based on pathological classification, esophageal carcinoma is mainly divided into squamous cell carcinoma, adenocarcinoma and other rare types (74). Several researches had been conducted to investigate the role of circFNDC3B in the malignant progression of esophageal cancer by Luo et al, Tang et al, and Wang et al (75)(76)(77).…”
Section: Esophageal Cancermentioning
confidence: 99%
“…So far, few exosomal circRNAs have been found to be involved in the metabolic reprogramming of cancer cells. For example, four exosomal circRNAs, circPDK1 [ 76 ], circ-RNF121 [ 77 ], circ_0072083 [ 78 ], and circFNDC3B [ 79 ] promote glycolysis in cancer cells by acting as molecular sponges for miRNAs and thus contribute to cancer progression. Yang found that exosomes-derived hsa_circ_0085361 promoted glutamine metabolism in bladder cancer cells by up-regulating the expression of GLS by adsorbing miR-141-3p [ 80 ].…”
Section: Circrna and Cancer Cell Metabolic Reprogrammingmentioning
confidence: 99%